2023
DOI: 10.1108/jbim-01-2022-0020
|View full text |Cite
|
Sign up to set email alerts
|

Effectual networking capability and SME performance in international B2B markets

Abstract: Purpose International entrepreneurship and marketing research reports the impact of effectual decision-making logic on small and medium-sized enterprises (SMEs) international performance. How the effectual logic of decision-making enhances the overall performance of SMEs in international business-to-business markets remains a puzzle in the field. The purpose of this study is to investigate the concept of networking capability as an important SME capability translating effectual decision-making into internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Previous research supports a positive relationship between effectuation and firm performance (e.g. Deligianni et al, 2017;Karami et al, 2023). Effectuation enhances small firms' performance in uncertain markets for several reasons.…”
Section: Effectuation and Firm Performancementioning
confidence: 90%
See 2 more Smart Citations
“…Previous research supports a positive relationship between effectuation and firm performance (e.g. Deligianni et al, 2017;Karami et al, 2023). Effectuation enhances small firms' performance in uncertain markets for several reasons.…”
Section: Effectuation and Firm Performancementioning
confidence: 90%
“…Effectuation builds on three types of personal means, including "who I am", "what I know" and "whom I know" (Sarasvathy, 2001;Van Mumford and Zettinig, 2022). The concept of effectual control empowers entrepreneurs to perceive uncertainty and the future in the context of their current resources, allowing them to devise strategies to expand their control over the situation by acquiring access to new resources (Karami et al, 2023;Sarasvathy, 2001). Entrepreneurs subsequently broaden their access to additional complementary resources through pre-commitments.…”
Section: Effectuationmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of partner countries relies on factors that drive collaborative operations, such as the determination of free trade policies, the management of infrastructure systems to support joint transportation and logistics activities, and so on (Rundh, 2022). Furthermore, Karami, Wooliscroft, and McNeill (2023) found that to successfully enter foreign markets, entrepreneurs must develop operational networks to create an environment that is alert and can deal with constantly emerging opportunities. From the above information, it can be concluded that when expanding into foreign markets, importers and exporters must rely on factors driving government policies, the country's infrastructure, and the organization's capability to develop through supply chain networks.…”
Section: Discussionmentioning
confidence: 99%
“…Given the size and importance of the B2B market, former studies have looked at the behavior of B2B companies [5][6][7][8][9]. However, many previous studies on corporate performance have been conducted without distinguishing between B2C and B2B [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%